EKSISTENSI IJMA’ KHASHAH (KONSENSUS KHUSUS) DAN KEABSAHANNYA SEBAGAI DALIL SYAR’I DALAM PENDIDIKAN HUKUM ISLAM - La Ode Ilman (IAIN TERNATE, 2019)
the purpose of this article to describe clearly about the validity of ijma’ khashah (local consensus)by ulama as Ad Dalil Asy Syar’i, perhaps most importantly can be used for helping are contemporary mujtahids when they conclude the islamic law expecially religious case that happen in every age and every time.The method of collecting data in this article is by literature review approach, and then many references refer to the classic book of ushul fiqih such asAl Bahr Al Muhith by Imam Az Zarkasyi, Al ‘Uddah Fii Usul Al Fiqhi by Qadhi Abu Ya’la, Al Ihkam Fii Usul Al Fiqhi by Al Amidy, Irsyad Al Fuhul by Imam As Syaukany, and Syarah Mukhtasar Ar Raudhah by Imam At Thufi.Object of discussion about the ijma’ khashah (local consensus) expecially in this article only focus on ijma’ khulafa Ar Rasyidin, ijma’ Madinah city population, ijma’ al aktsar (many people), ijma’ ahlul bait, dan ijma’ Asy Syaikhain.Beside that, each discussion in every topic the author explain method interpretation study based on the quality of dalil. Finally, the article can be concluded that the most of discussion about ijma’ khashah can’t be able or invalid for using as dalil syar’i in islamis law but the local consensus can be used to support and strengthen the Qur’an and Sunnah.